2003
DOI: 10.1046/j.1469-0691.2003.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of resistance in Pseudomonas aeruginosa obtained from patients with cystic fibrosis at different times

Abstract: A trend towards an increase of the MICs against antipseudomonal agents was observed over a limited period of time. It is necessary to prevent this development possibly by employing suitable combinations of antibiotics and the introduction of new substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
(20 reference statements)
4
7
0
Order By: Relevance
“…Hence, our results could provide a pharmacologic explanation for the increase in the ciprofloxacin MIC against P. aeruginosa secondary to ciprofloxacin treatment that was evidenced in children with cystic fibrosis. 5 Of note, this progressive decrease in the susceptibility to ciprofloxacin specifically involved bacterial strains with a baseline MIC greater than 0.125 mg/L, which seems to confirm the results of our simulations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Hence, our results could provide a pharmacologic explanation for the increase in the ciprofloxacin MIC against P. aeruginosa secondary to ciprofloxacin treatment that was evidenced in children with cystic fibrosis. 5 Of note, this progressive decrease in the susceptibility to ciprofloxacin specifically involved bacterial strains with a baseline MIC greater than 0.125 mg/L, which seems to confirm the results of our simulations.…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed that the current ciprofloxacin dosage recommendations are probably suboptimal in patients with cystic fibrosis-more specifically, for ciprofloxacin MICs higher than 0.125 mg/L against P. aeruginosa, which is lower than the clinical breakpoint of 0.5 mg/L defined by the European Society of Clinical Microbiology and Infectious Diseases 27 -as evidenced by an increase in the geometric mean of the MIC in patients with cystic fibrosis. 5 Thus, it appears that a clinically relevant proportion of children with cystic fibrosis who have infections due to P. aeruginosa may receive suboptimal treatment, even if the bacterial strain is considered susceptible to ciprofloxacin (according to the European guidelines 27 ). Hence, our results could provide a pharmacologic explanation for the increase in the ciprofloxacin MIC against P. aeruginosa secondary to ciprofloxacin treatment that was evidenced in children with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We noticed several cases of acute renal failure in our adult patients associated with the concurrent use of potentially nephrotoxic antibiotics, and this was also reported elsewhere. 4,5 The increasing prevalence of antibiotic multiresistance in Pseudomonas aeruginosa strains in CF patients, 6,7 and in particular that associated with epidemic strains, 8,9 may increase the requirements for nephrotoxic antibiotics. Indeed, the most prevalent epidemic strain in the United Kingdom (UK) (the Liverpool epidemic strain; LES) 10 is common in our unit and is frequently sensitive only to tobramycin and colistin sulphomethate, 11 both of which are potentially nephrotoxic.…”
Section: Introductionmentioning
confidence: 99%
“…Extended or continuous infusions increased the PTA for pathogens with elevated MIC, even as high as 8 to 12 μg/mL . This is invaluable in patients with CF because they usually have a history of previous exposure to antibiotics for both acute and chronic respiratory infections . Likely due to their repeated antibiotic exposures, reported antibiotic resistance rates are higher in children with CF.…”
Section: Clinical Pharmacology Optimizing Bedside Care Of Pediatric Imentioning
confidence: 99%